ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE - Dilinanda, Cynthia Anabella; Laturette, Kazia (Media Akuntansi dan Perpajakan Indonesia, 2023)
This study aims to determine the effect of independent commissioners, audit committees, managerial ownership and corporate social responsibility on tax avoidance with profitability as the control variable. The population in this study are companies listed on the SRI-KEHATI index in 2018–2019. The sample in this study were 27 companies in 2018 and 26 companies in 2019 so as to produce 53 data on companies listed on the SRIKEHATI index which were selected by purposive sampling. After conducting outliers, the research sample obtained was 49 samples of companies listed on the SRI-KEHATI index. The results of this study indicate that the mechanism of good corporate governance consisting of independent commissioners, audit committees and managerial ownership has a significance value of > 0.05. Based on these results, it can be concluded that the mechanism of good corporate governance consisting of independent commissioners, audit committees and managerial ownership has no significant effect on tax avoidance. Other results in this study indicate that corporate social responsibility has a significance value of <0.05 with a positive direction. Based on these results, it can be concluded that corporate social responsibility has a significant positive effect on tax avoidance. This is because corporate social responsibility is used as a tool to cover the company’s shortcomings or mistakes.